Seeing red: a political economy of digital memory. (September 2014) - Reading, Anna
This article intervenes into research on cultural and digital memory by arguing for the significance of the materiality of memory and its underlying political economy. Although cultural and digital memories are characterized as contested, multiple and often involving interplay and conflict between different power dynamics, what remains missing is an understanding of the material basis of digital, globally connective memory or what is termed here 'globital memory'. In work on memory which addresses social and mobile technologies there is an emphasis on the transition from collective to 'connective memory' and the ways in which social media offer possibilities for the articulation of marginalized memories, as well as new forms of archiving. While current concern is signalling a return to the question of the significance of 'mass media' in relation to social and mobile media and digital memory, this work does not yet address the political economy of 'globital' memory which includes the underlying materiality and technical infrastructure of social media. Using the conceptual metaphor of mining memories, the article will attend to what lies beneath the 'digital skin' of memories on social networks such as YouTube. I address the socioeconomic and technical infrastructures that enable the capture, circulation and storage of data that then become the raw material of globital memory.